ACCURACY OF SONOGRAPHIC ESTIMATION OF FETAL BIRTH WEIGHT IN 3 RD TRIMESTER TAKING POSTNATAL BIRTH WEIGHT AS GOLD STANDARD (The Research of Medical Science Review, 2025)
Objective: To assess the accuracy of sonographic fetal weight estimation in the third trimester by comparing it with actual birth weight and evaluating the impact of maternal and clinical factors on estimation precision. Methods: A prospective observational study was conducted on 180 pregnant women in their third trimester. Sonographic fetal weight estimation was performed using Hadlock’s formula based on biparietal diameter, head circumference, abdominal circumference and femur length. Actual birth weight was recorded within 30 minutes of delivery. Accuracy was defined as estimates within 10% of actual birth weight. The effect of maternal BMI, diabetes status, gestational age and scan-to- delivery interval on estimation accuracy was analyzed. Results: Sonographic estimates were within 10% of actual birth weight in 82.2% of cases. Accuracy was highest in the 2500–3500 g weight range (p = 0.048) but lower for low birth weight (<2500 g, p = 0.041) and macrosomic infants (>3500 g, p = 0.029). Maternal BMI ≥25 kg/m² (p = 0.027) and diabetes mellitus (p = 0.013) were associated with reduced accuracy. Gestational age influenced accuracy, with the best predictions at 38–39 weeks (81%). The scan-to-delivery interval significantly influenced the accuracy, with highest reliability within 3 days (90%, p = 0.010) but declining to 50% after 7 days (p = 0.048). Conclusion: Sonographic fetal weight estimation is highly accurate in most cases but less reliable for extremes of birth weight, higher maternal BMI and diabetic pregnancies. The timing of ultrasound relative to delivery is critical and alternative methods should be considered for high-risk cases.